PENGARUH LATIHAN LARI INTERVAL (INTERVAL RUNNING) TERHADAP KECEPATAN LARI PADA SSB PTPN V U-15 PERHENTIAN RAJA - Akwila Getsemani Siburian; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The aim of this study was to find out how much influence interval running training had on running speed at PTPN V U-15 Perhentian Raja SSB. This research was conducted in the PTPN V U-15 Perhentian Raja SSB field, Jalan Rambutan, Senapelan District in January-May 2023. In this study, researchers used a one group pretest-posttest design. The desired data in this study were carried out two tests, namely the initial test (pre-test) before doing interval running and the final test (post-test), after doing interval running training for 16 meetings three times a week with a sample size of 21 people. . Data from each group were taken from two measurements, namely the pre-test before the treatment and the post-test after the treatment was given. This aims to obtain research data that will be processed to test the hypothesis. Based on research conducted on 21 sample people by doing a pretest (initial test) running 40 yards. Then proceed with the treatment of interval running exercises for 16 meetings, after which a post-test (40 yards run) is carried out, the results obtained from the pre-test and post-test are analyzed by t-test. The results of hypothesis testing show that the tcount is 7.364 with a ttable of 1.725, so H_0 is rejected, H_a is accepted, at the alpha (α) level of 0.05. It can be concluded that there is an effect of interval running training on running speed at SSB PTPN V U-15 Perhentian Raja.Keywords: Effect of Interval Running Training, Running Speed